Comparative study between calcium gluconate with diosmin, cabergoline, and cabergoline with diosmin in prevention of ovarian hyperstimulation syndrome in high-risk women undergoing intracytoplasmic sperm injection (ICSI) procedures - Abdallah, Aya M.; Hussien, Amal K.; Alarfaj, Sumaiah J.; Elmasry, Thanaa A.; Kamal, Marwa; Sarhan, Hatem; Mosbeh, Mohammed H.; Sadek, Eman Mohamed (Frontiers in Pharmacology, 2025)
BackgroundOvarian Hyper-stimulation Syndrome (OHSS) is the main iatrogenic problem linked to ovarian stimulation with reproductive medications. Increased vascular permeability is considered the cause of OHSS. It leads to excess fluid flowing from blood vessels into surrounding tissue. Serious consequences include imbalances in electrolytes and impairment of the heart, liver, and kidneys.ObjectivesThis study aims to the comparison of the efficacy of calcium gluconate and diosmin combination, cabergoline alone, and a combination of cabergoline and diosmin in preventing OHSS in high-risk individuals undergoing intracytoplasmic sperm injection (ICSI) procedures.MethodsA prospective, randomized, single-blind, interventional study was carried out on 180 high-risk females for OHSS. They were divided into three groups, each with 60 women: Group A received IV infusion of calcium gluconate and diosmin. Group B received cabergoline alone. Group C received cabergoline and diosmin. Patients were regularly evaluated using clinical examinations and ultrasound to check for signs of OHSS. The main outcome was the frequency of moderate to severe OHSS. Secondary outcomes were the rates of clinical pregnancy, miscarriage, and live birth.ResultsThe research demonstrated that there was no significant difference in the prevalence of mild OHSS among the three groups (p-value = 0.91for each). Nevertheless, the three groups showed a notable difference in the occurrence of moderate OHSS (p = 0.044) respectively. Notably, severe ovarian hyper-stimulation syndrome wasn’t observed in Group C. However, 13.3% of patients in Group B and 6.6% in Group A were affected with a highly significant difference (p = 0.007). The chemical and clinical pregnancy rates across the three groups did not demonstrate any statistically significant differences (p-value of 0.53), (p-value of 0.17) correspondingly).ConclusionOur study found that using cabergoline and diosmin together in high-risk females undergoing ICSI procedures was significantly more successful in preventing OHSS compared to using calcium gluconate and diosmin or cabergoline alone. This combination did not impact miscarriage, pregnancy rate, or the likelihood of multiple pregnancy.Clinical Trial Registrationidentifier NCT06333691.